Serum Creatinine and Serum Cystatin C are Both Relevant Renal Markers to Estimate Vancomycin Clearance in Critically Ill Neonates - Leroux, Stéphanie; Biran, Valérie; van den Anker, John; Gotta, Verena; Zhao, Wei; Zhang, Daolun; Jacqz-Aigrain, Evelyne; Pfister, Marc (Frontiers in Pharmacology, 2021)
Purpose. Serum creatinine (SCr) is used as a marker of kidney function to guide dosing of renally eliminated drugs. Serum Cystatin C (S-CysC) has been suggested as a more reliable kidney marker than SCr in adults and children. Purpose of this study was to investigate S-CysC as alternative renal marker to SCr for estimating vancomycin clearance in neonates undergoing intensive care. Methods. Vancomycin pharmacokinetics (PK), SCr and S-CysC data were collected in patients undergoing vancomycin treatment in the neonatal intensive care unit of Robert Debré Hospital - Paris. A population PK analysis was performed utilizing routine therapeutic drug monitoring samples. S-CysC and SCr were compared as covariates on vancomycin clearance using stepwise covariate modeling (forward inclusion [p<0.05] and backward elimination [p<0.01]). Model performance was evaluated by graphical and statistical criteria. Results. A total of 108 vancomycin concentrations from 66 patients (postmenstrual age [PMA] of 26 to 46 weeks) were modeled with an allometric one-compartment model. The median (range) values for SCr and S-CysC were 41 (12 to 153) µmol/L and 1.43 (0.95 to 2.83) mg/L, respectively. Following stepwise covariate model building, SCr was retained as single marker of kidney function (after accounting for weight and PMA) in the final model. Compared to the final model based on SCr, the alternative model based on S-CysC showed very similar performance (e.g. BIC of 578.3 vs 576.4) but included one additional covariate: impact of mechanical ventilation on vancomycin clearance, in addition to the effects of size and maturation. Conclusion. SCr and S-CysC are both relevant renal markers for individualization of vancomycin dosing in critically ill neonates. However, if using S-CysC for this purpose mechanical ventilation needs to be taken into account.